TINJAUAN LITERATUR SEMANGAT WIRAUSAHA SOSIAL KADER PKK DALAM PEMBERDAYAAN EKONOMI KELUARGA - Natalia Sari Pujiastuti (Universitas Diponegoro, 2024)
This research analyses the spirit of social entrepreneurship among the administrators of Empowerment and Family Welfare Organizations (PKK Cadres) through the Family Income Enhancement Program (UP2K-PKK). Detailing the concept of social entrepreneurship through a literature review, the study seeks to understand how the spirit of social entrepreneurship can act as a catalyst for family economic empowerment. The literature analysis covers the characteristics of social entrepreneurship, the role of PKK Cadres in the implementation of UP2K-PKK, and its impact on community development. The hope is that the results of this research can provide in-depth insights into the contribution of the spirit of social entrepreneurship in enhancing the effectiveness of UP2K-PKK. Additionally, the research findings are expected to serve as a foundation for strengthening the role of PKK cadres in realizing family economic empowerment programs.Keyword: Family Income; Kader PKK; UP2K-PKK; Social EntrepeneurshipPenelitian ini menganalisis semangat wirausaha sosial di kalangan Kader PKK melalui Program Usaha Peningkatan Pendapatan Keluarga (UP2K-PKK). Merinci konsep wirausaha sosial melalui tinjauan literatur, penelitian ini bertujuan memahami sejauh mana semangat wirausaha sosial dapat menjadi katalisator bagi pemberdayaan ekonomi keluarga. Analisis literatur mencakup karakteristik wirausaha sosial, peran Kader PKK dalam implementasi UP2K-PKK, dan dampaknya terhadap pembangunan komunitas. Diharapkan hasil penelitian ini dapat memberikan wawasan mendalam tentang kontribusi semangat wirausaha sosial dalam meningkatkan efektivitas UP2K-PKK, serta menjadi landasan untuk memperkuat peran Kader PKK dalam merealisasikan program pemberdayaan ekonomi keluarga.Kata kunci: Ekonomi Keluarga; Kader PKK; UP2K-PKK; Wirausaha Sosial